Treatment of Localized and Locally Advanced, High-Risk Prostate Cancer: A Report From the First Prostate Cancer Consensus Conference for Developing Countries. (2021) - Khauli, Raja; Ferrigno, Robson; Guimarães, Gustavo; Bulbulan, Muhammad; Uson Junior, Pedro Luiz Serrano; Salvajoli, Bernardo; Palhares, Daniel Moore Freitas; Racy, Douglas; Gil, Erlon; de Arruda, Fernando Freire; Lemos, Gustavo Caserta; Carvalhal, Gustavo Franco; et al.
Abstract : PURPOSE: To generate and present survey results on important issues relevant to treatment and follow-up of localized and locally advanced, high-risk prostate cancer (PCa) focusing on developing countries. METHODS: A panel of 99 PCa experts developed more than 300 survey questions of which 67 questions concern the main areas of interest of this article: treatment and follow-up of localized and locally advanced, high-risk PCa in developing countries. A larger panel of 99 international multidisciplinary cancer experts voted on these questions to create the recommendations for treatment and follow-up of localized and locally advanced, high-risk PCa in areas of limited resources discussed in this article. RESULTS: The panel voted publicly but anonymously on the predefined questions. Each question was deemed consensus if 75% or more of the full panel had selected a particular answer. These answers are based on panelist opinion and not on a literature review or meta-analysis. For questions that refer to an area of limited resources, the recommendations considered cost-effectiveness as well as the possible therapies with easier and greater access. Each question had five to seven relevant answers including two nonanswers. Results were tabulated in real time. CONCLUSION: The voting results and recommendations presented in this article can guide physicians managing localized and locally advanced, high-risk PCa in areas of limited resources. Individual clinical decision making should be supported by available data; however, as guidelines for treatment of localized and locally advanced, high-risk PCa in developing countries have not been defined, this article will serve as a point of reference when confronted with this disease.